Intervensi untuk Mengatasi Gangguan Perilaku Menentang Anak dengan Parent Management Training - Hairina, Yulia (IAIN Antasari Banjarmasin, 2013)
Parent Management Training, in psychology, is one of the intervention for parents in solving problems, especially parents whose children with opposing behavior disorder. This method of training employs behaviour modification technique and the principals of individual study process in changing behavior, that is, in this writing, childrenâs opposing behavior. In the Parent Management Training program, parents will be trained to be a trainer or therapist in which the assumption they have is the biggest potential to change the childrenâs behavior for they have the biggest control to the important aspects in childrenâs natural environment. Besides that, it will enable the children to actualize their newly learned behavior since they do not have to undergo the process received by the therapists into their homes. The focus in solving problems through the Parent Management Training approach is on dyadic relationship and the behavior symptoms is the base in performing intervention. In this particular intervention, parents and therapists work together, in which parents must be willing to do the program that has been compiled in order to change the targetâs behavior.